Transformational Leadership and Follower's Perceived Group Cohesiveness: Mediating Role of Follower's Karma-yoga. Issue 2 (May 2021) - Muppidathi, Ponmythili; Krishnan, Venkat R.
This article looks at the relationship between five sub-dimensions of transformational leadership (idealised influence attributed, idealised influence behaviour, inspirational motivation, intellectual stimulation and individualised consideration), follower's karma-yoga and follower's perceived group cohesiveness. Data were collected in a research and development organisation in India, from 771 employees (561 male and 210 female) with minimum 5 years of work experience in that organisation. Partial least squares structural equation modelling PLS-SEM analysis shows that four sub-dimensions of transformational leadership—idealised influence attributed, idealised influence behaviour, inspirational motivation, and intellectual stimulation—are positively related to follower's perceived group cohesiveness. In addition, this relationship is partially mediated by the follower's karma-yoga. Focusing on increasing the frequency of idealised influence attributed, idealised influence behaviour, inspirational motivation and intellectual stimulation of managers will result in making the employees more karma-yoga oriented; both these will result in increasing the follower's perceived group cohesiveness in the organisation, making the work environment more harmonious and productive.